A review of photobiomodulation and its application in dentistry - Shruti Soni; Sahil Thakar (Wolters Kluwer Medknow Publications, 2022)
Photobiomodulation (PBM), which is further termed as low-level laser therapy is a noninvasive type of therapy. It uses a certain wavelength of red and infrared light and brings about many physiological effects in cells and tissues which establish the basis of PBM. This light therapy photochemically triggers the cells and results in the production of molecules for example, adenosine triphosphate, reactive oxygen species, calcium ions, etc., This further contributes to cell proliferation, differentiation, and migration. PBM contributes in alleviating pain, promotes tissue healing and also has an anti-inflammatory effect on targeted tissues. Research on PBM began back in the 1960s and various studies conducted in the past documented that this therapy has many applications in various specialties of dentistry. Till date, further studies are being conducted to discover more beneficial properties of this therapy. This therapy can be used for the treatment of multitudinous conditions of the oral cavity such as aphthous ulcers, herpes, pemphigus, burning mouth syndrome, and many more conditions, it can mitigate the pain following the orthodontic treatment, can be used to deal with the temporomandibular disorders (TMDs), alleviate dental pains, enhances the depth of anesthesia and many more uses in dentistry.